Isolation of Aspergillus from edible-nest swiftlet feces in bird houses of Central Java - Ningrum, Siti Gusti; Ginting, Eykel Arief Fortuna; Rahmawati, Indra (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2024)
Five edible-nest swiftlet houses in Central Java were sampled for fecal specimens. The samples were obtained using a sterile container to maintain aseptic conditions. Subsequently, the samples were mixed thoroughly in a tube containing sterile saline and allowed to incubate for a duration of 30 minutes. One milliliter of supernatant was placed onto Potato Dextrose Agar (PDA) with chloramphenicol (50 mg/L) and incubated at a temperature of 25 ºC for a duration of one week. The results showed that all samples had a high percentage of Aspergillus niger (100%), Aspergillus flavus (100%), and Aspergillus fumigatus (100%) isolates. The findings suggest that edible-nest swiftlet houses in Central Java can serve as a potential reservoir and conduit for fungal infection and transmission.